New constraints on the Pb and Nd isotopic evolution of NE Atlantic water masses - Muiños, S.B.; Frank, Martin; Maden, C.; Hein, J.R.; Flierdt, Tina van de; Lebreiro, S.M.; Gaspar, L.; Monteiro, J.H.; Halliday, Alex N. (Geochemistry, Geophysics, Geosystems, 2008)
ISSN:1525-2027